Relationship between High School Principals' Humor Styles and Teacher Leadership - Kılınç, Ali Çağatay; Recepoğlu, Ergün; Koşar, Serkan (Macrothink Institute, Inc., 2014)
This study aimed at examining the relationship between high school teachers' perceptions of teacher leadership and school principals' humor styles. A total of 252 teachers employed in 12 high schools located in the city centre of Ankara, Turkey participated in the study. “The Humor Behavior Scale” developed by Cemaloglu, Recepoglu, Sahin, Dasci and Kokturk (2013) and “The Teacher Leadership Scale” developed by Beycioglu and Aslan (2010) were used to gather data. Results of the study indicated that productive-social humor style was positively and significantly correlated with such dimensions of teacher leadership as institutional improvement, professional improvement, and collaboration among colleagues. Results also revealed that the productive-social humor style was a significant predictor of institutional improvement and professional improvement. Results were discussed within the context of the improvement of the leadership behaviors of teachers.
Keywords: 4. Education